If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 4x(2x + -10) + 6(x + -3) = 2(x + -2)(4x + -11) + -20 Reorder the terms: 2x + 4x(-10 + 2x) + 6(x + -3) = 2(x + -2)(4x + -11) + -20 2x + (-10 * 4x + 2x * 4x) + 6(x + -3) = 2(x + -2)(4x + -11) + -20 2x + (-40x + 8x2) + 6(x + -3) = 2(x + -2)(4x + -11) + -20 Reorder the terms: 2x + -40x + 8x2 + 6(-3 + x) = 2(x + -2)(4x + -11) + -20 2x + -40x + 8x2 + (-3 * 6 + x * 6) = 2(x + -2)(4x + -11) + -20 2x + -40x + 8x2 + (-18 + 6x) = 2(x + -2)(4x + -11) + -20 Reorder the terms: -18 + 2x + -40x + 6x + 8x2 = 2(x + -2)(4x + -11) + -20 Combine like terms: 2x + -40x = -38x -18 + -38x + 6x + 8x2 = 2(x + -2)(4x + -11) + -20 Combine like terms: -38x + 6x = -32x -18 + -32x + 8x2 = 2(x + -2)(4x + -11) + -20 Reorder the terms: -18 + -32x + 8x2 = 2(-2 + x)(4x + -11) + -20 Reorder the terms: -18 + -32x + 8x2 = 2(-2 + x)(-11 + 4x) + -20 Multiply (-2 + x) * (-11 + 4x) -18 + -32x + 8x2 = 2(-2(-11 + 4x) + x(-11 + 4x)) + -20 -18 + -32x + 8x2 = 2((-11 * -2 + 4x * -2) + x(-11 + 4x)) + -20 -18 + -32x + 8x2 = 2((22 + -8x) + x(-11 + 4x)) + -20 -18 + -32x + 8x2 = 2(22 + -8x + (-11 * x + 4x * x)) + -20 -18 + -32x + 8x2 = 2(22 + -8x + (-11x + 4x2)) + -20 Combine like terms: -8x + -11x = -19x -18 + -32x + 8x2 = 2(22 + -19x + 4x2) + -20 -18 + -32x + 8x2 = (22 * 2 + -19x * 2 + 4x2 * 2) + -20 -18 + -32x + 8x2 = (44 + -38x + 8x2) + -20 Reorder the terms: -18 + -32x + 8x2 = 44 + -20 + -38x + 8x2 Combine like terms: 44 + -20 = 24 -18 + -32x + 8x2 = 24 + -38x + 8x2 Add '-8x2' to each side of the equation. -18 + -32x + 8x2 + -8x2 = 24 + -38x + 8x2 + -8x2 Combine like terms: 8x2 + -8x2 = 0 -18 + -32x + 0 = 24 + -38x + 8x2 + -8x2 -18 + -32x = 24 + -38x + 8x2 + -8x2 Combine like terms: 8x2 + -8x2 = 0 -18 + -32x = 24 + -38x + 0 -18 + -32x = 24 + -38x Solving -18 + -32x = 24 + -38x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '38x' to each side of the equation. -18 + -32x + 38x = 24 + -38x + 38x Combine like terms: -32x + 38x = 6x -18 + 6x = 24 + -38x + 38x Combine like terms: -38x + 38x = 0 -18 + 6x = 24 + 0 -18 + 6x = 24 Add '18' to each side of the equation. -18 + 18 + 6x = 24 + 18 Combine like terms: -18 + 18 = 0 0 + 6x = 24 + 18 6x = 24 + 18 Combine like terms: 24 + 18 = 42 6x = 42 Divide each side by '6'. x = 7 Simplifying x = 7
| 16=4x-6(5x+32) | | 32+y=47 | | 222+6x=-3x-156 | | x+-24=-9 | | 6(z-4)+6z-2= | | 2b+9=6b-5 | | 9r^2+12r+13=0 | | 7a-3=2a+12 | | 3x^5+5x^3+15x-8=0 | | 0.5/0.666 | | -.5m-5=-4 | | 8r(r+2)= | | 72-5x=37 | | 5x-(10x-6)= | | -2+3x=.6+x | | (2x+10)=(5x-26) | | 9.7x=33.55 | | 2x-3y=5x+6 | | (x-5)+4x=180 | | 13st-3st+6st-9st= | | -4m-8=8 | | -.5(c+3)=-7 | | 5(1x+7)=50 | | 5*17^2/103 | | -1/2=x-2/3 | | v=14000t+20000 | | 8a^3-5a^2+4a^3= | | h(t)=-16t^2+784 | | 6(4x+8)=144 | | 5(17)^2/103= | | 4x+-3=x+9 | | -5+x=7-3x |